THE IMAGE OF WOMEN IN THE POETRY OF KAMALA DAS AND SYLVIA PLATH - Chandrakar, Durga (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The word ’Image’ has one or two or both meanings: one, as the character of a thing or person as received by the public, two, a mental representation, idea or conception. The application of this term can be either literal or figurative, but when conjoined with literature it can be both. The broadly general image of women in literature identifies the real status accorded to woman in society- as mother, wife, daughter, in that order in a familial setting. Outside it, she is the prostitute, the widow, the companion etc. In more modern times she is accepted as a professional, but when she protests against injustice and exploitation she is grudgingly termed activist and seen as rebel or deviant.